Complement Genetic Variants and FH Desialylation in S. pneumoniae-Haemolytic Uraemic Syndrome - Gómez Delgado, Irene; Corvillo, Fernando; Nozal, Pilar; Arjona, Emilia; Madrid, Álvaro; Melgosa, Marta; Bravo, Juan; Szilágyi, Ágnes; Csuka, Dorottya; Veszeli, Nóra; Prohászka, Zoltán; Sánchez-Corral, Pilar (Frontiers in Immunology, 2021)
Haemolytic Uraemic Syndrome associated with Streptococcus pneumoniae infections (SP-HUS) is a clinically well-known entity that generally affects infants, and could have a worse prognosis than HUS associated to E. coli infections. It has been assumed that complement genetic variants associated with primary atypical HUS cases (aHUS) do not contribute to SP-HUS, which is solely attributed to the action of the pneumococcal neuraminidase on the host cellular surfaces. We previously identified complement pathogenic variants and risk polymorphisms in a few Hungarian SP-HUS patients, and have now extended these studies to a cohort of 13 Spanish SP-HUS patients. Five patients presented rare complement variants of unknown significance, but the frequency of the risk haplotypes in the CFH-CFHR3-CFHR1 region was similar to the observed in aHUS. Moreover, we observed desialylation of Factor H (FH) and the FH-Related proteins in plasma samples from 2 Spanish and 4 Hungarian SP-HUS patients. To analyze the functional relevance of this finding, we compared the ability of native and “in vitro” desialylated FH in: (a) binding to C3b-coated microtiter plates; (b) proteolysis of fluid-phase and surface-bound C3b by Factor I; (c) dissociation of surface bound-C3bBb convertase; (d) haemolytic assays on sheep erythrocytes. We found that desialylated FH had reduced capacity to control complement activation on sheep erythrocytes, suggesting a role for FH sialic acids on binding to cellular surfaces. We conclude that aHUS-risk variants in the CFH-CFHR3-CFHR1 region could also contribute to disease-predisposition to SP-HUS, and that transient desialylation of complement FH by the pneumococcal neuraminidase may have a role in disease pathogenesis.